PENCAPAIAN VAKSINASI COVID-19 PADA LANSIA BERDASARKAN DUKUNGAN KELUARGA - Yenni Yenni; Rita Febriyanti Putri (Ensiklopedia of Journal, 2022)
The achievement of COVID-19 vaccination for elderly is still low. This study aims to determine the relationship between family support and the achievement of COVID-19 vaccination in the elderly in the Sunagai Sariak Public Health Center, Padang Pariaman Regency. This type of research is descriptive analytic with a cross sectional approach that has been carried out in September 2022 involving 97 respondents who were taken by simple random sampling. Data collection in the form of questionnaires. Data analysis using chi square test results of the study showed that 51,5% vaccine achievement was not achieved and 53,6% with good family support. There was a relationship between family support and vaccination achievement COVID-19 in the elderly (p=0,0005). Concluded that family support is a variable related to the achievement of the COVID-19 vaccine in the elderlyKeywords: COVID-19 vaccine achievement, elderly, Family support.